Методологічні підходи до оцінювання впливу цифрової трансформації на сталий розвиток - Червінська Т. М.; Chervins'ka, Tetiana (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Обгрунтовано методологічний інструментарій щодо оцінки впливу цифрової трансформації на сталість розвитку економічних систем. Комплексно проаналізовано сучасні критерії оцінювання означених процесів, зокрема, індекси цифрової зрілості, системно-динамічне виявлення взаємозв’язку цифровізації і сталого розвитку. Запропоновано використання комплексної системи оцінки на основі сучасних індикаторних підходів та кількісних критеріїв, а також матричного підходу. Окреслено можливі напрями удосконалення методології оцінки на основі застосування індикаторів кіберстійкості і екологічної ефективності цифрової інфраструктури. Практична результативність запропонованих підходів полягає у можливостях їх використання різними управлінськими структурами задля коригування стратегій цифрового розвитку з огляду на пріоритетність сталого зростання. /// EN: The article examines comprehensive methodological approaches to assessing the impact of digital transformation on sustainable development processes in the context of global challenges and military actions in Ukraine. The relevance of the issue is determined by the importance of objectively assessing the synergistic effect of introducing information and communication technologies into the social, economic and environmental spheres. The author analyses modern methodological tools, in particular digital maturity indices and system-dynamic analysis of the relationship between digitalisation and sustainable development goals. Particular attention is paid to Ukraine's experience in forming a national system for monitoring digital transformations. The methodology for calculating the Regional Digital Transformation Index and the tools for assessing the digital maturity of local communities are considered. The paper proves that a high level of digitalisation is a key factor in the stability of state institutions and communities, ensuring the continuity of public services and transparency of resource management even in crisis conditions. Approaches to assessing the digital potential of Ukrainian enterprises based on the use of modern indicator methods and a system of quantitative indicators are proposed. The importance of a matrix approach is outlined, which allows companies to transition to proactive decision-making, ensure the optimisation of operational processes and increase efficiency. It is determined that the modern Ukrainian assessment model successfully focuses on institutional capacity and service accessibility, but requires further integration of green transition indicators. Proposals are formulated to improve the assessment methodology by including indicators of cyber resilience and environmental efficiency of digital infrastructure. The practical significance of the results obtained lies in the possibilities of their use by state and local authorities to adjust digital development strategies in view of sustainable growth priorities. The proposed approaches will contribute to more effective attraction of international investment through digital recovery platforms.
Methodologies for assessing the impact of digital transformation on sustainable development
Keywords: цифрова трансформація; сталий розвиток; методологія оцінювання; індекс цифрової трансформації; цифрова зрілість; стійкість; digital transformation; sustainable development; assessment methodology; digital transformation index; digital maturity; sustainability